Analisis Faktor-Faktor yang Mempengaruhi Disiplin Kerja Guru di MAN 2 Kota Bukittinggi - Asmira, Asmira; Fetri, Yuhana; Asmu’i, Muhammad; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2024)
Teacher work discipline is one of the important factors in realizing an effective and quality teaching and learning process in schools. This study aims to analyze the factors that affect teacher work discipline in MAN 2 Bukittinggi city. This study uses a qualitative approach with a literature review method. Data collection is carried out through various literature, namely scientific articles sourced from Google Scholar, books, and other documents relevant to the fokus of this research. Data collection was carried out online using the keyword "teacher work discipline". Data analysis is carried out descriptively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the most dominant factors affecting teachers' work discipline in MAN 2 Bukittinggi City are work motivation, teacher welfare, and school leadership. Other factors such as teacher commitment, teacher competence, teacher health, school culture, work environment, and government policies also have a significant influence on teacher work discipline